Case report: Multimodality imaging revealing ruptured giant coronary artery aneurysm presenting with hemoptysis - Gong, Xiangfeng; Zhang, Hongwei; Peng, Wanlin; Yang, Gang; Xiao, Zhenghua (Frontiers in Cardiovascular Medicine, 2023)
Giant coronary artery aneurysm (CAA) is a relatively uncommon disease that is defined by a focal dilation of at least 20 mm and characterized by various clinical symptoms. However, cases presenting primarily with hemoptysis have not been reported. A man in his late 20 s suffering from persistent chest pain for over 2 months was transferred to our emergency department for intermittent hemoptysis lasting for 12 h. Bronchoscopy detected fresh blood in the left upper lobe bronchus without a definite bleeding source. Magnetic resonance imaging (MRI) demonstrated a heterogeneous mass and the high-intensity signals suggested active bleeding. coronary computed tomography (CT) angiography demonstrated a giant ruptured CAA wrapped in a large mediastinal mass Coronary angiography confirmed the CAA originating from the left anterior descending artery. The patient underwent an emergency sternotomy and an enormous hematoma arising from a ruptured CAA densely adhering to the left lung was identified. The patient recovered uneventfully and was discharged on the 7th day later. The ruptured CAA masquerading as hemoptysis highlights the indispensability of multimodality imaging for accurate diagnosis. Urgent surgical intervention is desirable in such life-threatening conditions.